Effect of indomethacin on hyperthermia induced by heat stress in broiler chickens - Furlan, R. L.; Macari, Marcos [UNESP]; Malheiros, E. B.; Secato, E. R.; Guerreiro, JR (Springer, 1998)
An investigation was carried out to verify whether the heat stress hyperthermia response of broilers is prostaglandin-dependent. Male broiler chickens of the Hubbard-Petterson strain, aged 35-49 days, were used. Chickens were injected with indomethacin (1 mg/kg intraperitoneally) 15 min before or 2 h after heat exposure (at 35 degrees C for 4 h), and rectal temperature was measured before injection and up to 4 h thereafter. Birds were separated into two groups with and without access to water during heat stress. The increase in rectal temperature was lower (P<0.05) in birds with access to drinking water during heat exposure. All birds injected with indomethacin exhibited an increase in rectal temperature, irrespective of whether indomethacin was administered before or in the course of the rise in temperature. The results revealed that the increase in rectal temperature during heat exposure is not prostaglandin-dependent, and that the use of cyclooxigenase inhibitors is not recommended to attenuate heat stress hyperthermia in broiler chickens.
Keywords: indomethacin; hyperthermia; heat stress; broilers